ANALISIS GAYA KEPEMIMPINAN SEKRETARIS DAERAH DALAM MENINGKATKAN DISIPLIN DAN SEMANGAT KERJA PEGAWAI DI KANTOR SEKRETARIAT DAERAH KABUPATEN NIAS SELATAN - ZAMILI, RITA ERNAWATI; SILABAN, PANTAS H.; HUTAHAEAN, MARLAN (JURNAL ILMIAH SIMANTEK, 2023)
This study aims to describe the leadership style of the Regional Secretary in increasing the discipline and morale of employees at the Regional Secretariat office of South Nias Regency. This form of research uses a qualitative approach with a descriptive type. This research was conducted at the Regional Secretariat Office of South Nias Regency. Collecting research data through interviews, observation and documentation. Based on the results of the research, several conclusions can be put forward, namely 1) South Nias District Secretary applies a motivational, situational and democratic leadership style, 2) Employee presence and obedience to ASN work regulations are classified as good, this is because employees pay attention or do not neglect work regulations. Even though there are still employees who do not complete their work on time as stipulated, there are still employees who like to be late and leave the office earlier, and 3) The morale of the employees of the South Nias Regency Regional Secretariat office is quite good due to the motivation and attention of the leadership, a comfortable work environment and no pressure, the leadership style adopted by the leadership is democratic, and motivating and the leadership respects the work of subordinates and employees realize that the tasks assigned to them will be accounted for before God.